2020
DOI: 10.3389/fphar.2020.00692
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Protective Actions of Cat’s Whiskers (Misai Kucing) on the Central Nervous System

Abstract: Orthosiphon stamineus (OS) or Orthosiphon aristatus var. aristatus (OAA) is commonly known as cat's whiskers or "misai kucing". It is an herbaceous shrub that is popular in many different traditional and complementary medicinal systems. Its popularity has been justified by the plethora of studies that have shown that the secondary metabolites of the plant has effects that range from anti-inflammatory and gastroprotective to anorexic and antihypertensive. As such, OS could also be a potential treatment for Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Different from Orthosiphol A, Rosmarinic acid, a water-soluble and absorbable polyphenol that been researched endlessly, had several exciting effects, including antioxidant(Shen et al, 2017), anti-inflammatory(Luo et al, 2020), anti-tumor(Kim et al, 2015), antimicrobial(Slobodnikova et al, 2013), anti-diabetic(Ngo et al, 2018), neuroprotective(Ghasemzadeh and Hosseinzadeh, 2020; Hasanein and Mahtaj, 2015) and nephroprotective activities(Domitrovic et al, 2014; Al-Dhabi et al, 2014) even cosmetic effects(Iwona and Katarzyna, 2020). Similarly, two flavonoids Eupatorin and Sinensetin also been confirmed to possess almost the same pharmacological effects as O. aristatus (Han et al, 2020; Laavola et al, 2012; Chung et al, 2020; Ashraf et al, 2018). Noteworthily, our results have shown that Rosmarinic acid cannot cross the blood-brain barrier and its gastrointestinal absorption was low (Table S2).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Different from Orthosiphol A, Rosmarinic acid, a water-soluble and absorbable polyphenol that been researched endlessly, had several exciting effects, including antioxidant(Shen et al, 2017), anti-inflammatory(Luo et al, 2020), anti-tumor(Kim et al, 2015), antimicrobial(Slobodnikova et al, 2013), anti-diabetic(Ngo et al, 2018), neuroprotective(Ghasemzadeh and Hosseinzadeh, 2020; Hasanein and Mahtaj, 2015) and nephroprotective activities(Domitrovic et al, 2014; Al-Dhabi et al, 2014) even cosmetic effects(Iwona and Katarzyna, 2020). Similarly, two flavonoids Eupatorin and Sinensetin also been confirmed to possess almost the same pharmacological effects as O. aristatus (Han et al, 2020; Laavola et al, 2012; Chung et al, 2020; Ashraf et al, 2018). Noteworthily, our results have shown that Rosmarinic acid cannot cross the blood-brain barrier and its gastrointestinal absorption was low (Table S2).…”
Section: Discussionmentioning
confidence: 84%
“…Noteworthily, our results have shown that Rosmarinic acid cannot cross the blood-brain barrier and its gastrointestinal absorption was low (Table S2). But the pre-clinical experiments showed that it can improve central system diseases such as epilepsy and Alzheimer’s disease(Ghasemzadeh and Hosseinzadeh, 2020; Hasanein and Mahtaj, 2015; Chung et al, 2020), which makes me confused. Anyway, we speculate that the O. aristatus own many ponderable ingredients for phytochemical screening and validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of studies on the crude extracts or secondary metabolites of OS has shown protective effects, including antioxidative, anti-inflammatory, antiproliferative, cytotoxic, and antiangiogenic effects [ 10 , 11 ]. Added to that, OS has recently been reported for its neuroprotective effects [ 12 ]. In another recent study, OS leaf proteins (OSLPs) alleviated pentylenetetrazol-induced seizures in adult zebrafish [ 13 ].…”
Section: Introductionmentioning
confidence: 99%